A dual source fed eleven level switched capacitor multilevel inverter with voltage boosting capability - Hussain, Md Tahmid; Tariq, Mohd; Sarwar, Adil; Ahmad, Shafiq; Poshtan, Majid; Mahmoud, Haitham A. (Frontiers in Energy Research, 2024)
This work introduces an 11-level switched-capacitor multilevel inverter (SCMLI) designed for solar photo-voltaic (PV) applications, capitalizing on the growing popularity of multilevel inverters due to their superior power quality. With a 1.67-times boosting capability, the proposed SCMLI employs 10 switches, 2 DC supplies, and 2 capacitors to achieve an 11-level output voltage waveform. The topology requires only seven driver circuits, incorporating 2 bidirectional switches and 3 complementary pairs of switches. The proposed inverter has intrinsic capacitor self-balancing features since the capacitors are connected across the DC voltage source at different times throughout a basic cycle to charge the capacitors at a level of input voltage. A thorough comparison between the topology and recently developed SCMLI’s has been presented. The comparison demonstrates the effectiveness in terms of switches, capacitors, sources, efficiency, total standing voltage (TSV), and boosting capacity. To experimentally validate its performance, the suggested SCMLI undergoes testing using a frequency-based switching method. The topology exhibits low total harmonic distortion (THD) of 7.65% in its output voltage waveform and 0.89% in the output current waveform.